2012
DOI: 10.1080/00207594.2011.647030
|View full text |Cite
|
Sign up to set email alerts
|

Culture, social class, and independence–interdependence: The case of Chinese adolescents

Abstract: Social class demarcates sociocultural environments differing in the relative abundance and scarcity of resources, which in turn differentially afford independent and interdependent psychological processes. The relationships between social class and psychological processes are well documented in Western populations but less so elsewhere. Examining such a relationship is particularly important in China, with its unique historical and sociocultural issues surrounding social class. This research examined the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…For instance, Cai and colleagues (2012) examined whether socioecological factors that have become prevalent in recent decades in China-affluence, urbanization, and single-child households-are predictive of one psychological process sometimes associated with individualism, namely, narcissism (Twenge et al, 2008). This research revealed that all three socioecological factors examined were independently predictive of narcissism-a higher score of narcissism was found among affluent (vs. less affluent) participants, those living in urban (vs. rural) areas, and those without (vs. with) siblings (see also Hamamura et al, 2013). However, these inferences have limitations- Yang (1996) interpreted such a tendency from a qualitative review of Chinese personality research, and Cai and colleagues inferred such a pattern from cross-sectional data obtained among contemporary Chinese participants.…”
Section: Patterns Of Cultural Change Across Societiesmentioning
confidence: 86%
“…For instance, Cai and colleagues (2012) examined whether socioecological factors that have become prevalent in recent decades in China-affluence, urbanization, and single-child households-are predictive of one psychological process sometimes associated with individualism, namely, narcissism (Twenge et al, 2008). This research revealed that all three socioecological factors examined were independently predictive of narcissism-a higher score of narcissism was found among affluent (vs. less affluent) participants, those living in urban (vs. rural) areas, and those without (vs. with) siblings (see also Hamamura et al, 2013). However, these inferences have limitations- Yang (1996) interpreted such a tendency from a qualitative review of Chinese personality research, and Cai and colleagues inferred such a pattern from cross-sectional data obtained among contemporary Chinese participants.…”
Section: Patterns Of Cultural Change Across Societiesmentioning
confidence: 86%
“…These theories suggest an interactive hypothesis regarding social class and social cognition: The cognitive tendencies of higher class people exemplify those of a society more so than the cognitive tendencies of lower class people. Comparable social class differences have been further observed in China (Hamamura, Xu, & Du, 2012), and among the Japanese younger adults (Kitayama et al, 2013). Higher class individuals in each culture would be more aligned with the culturally distinct ways of reasoning than lower class individuals.…”
Section: Social Class Culture and Cognitionmentioning
confidence: 94%
“…Hamamura et al (2013) reported the effect of parental educational attainment on adolescents' tendency toward independence-interdependence. The effects of the one-child policy have also been examined extensively (e.g., Lee, 1992; Fan et al, 1994; Wang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%